Literature Review: The Recent Midwifery Interventions Improving Public Attitudes and Knowledge in Stunting Prevention - Neli Sunarni; Annisa Tsania Rizqiyani; Liva Maita (Genius Midwifery Journal, 2022)
Introduction: Stunting is still a public health problem in developing countries such as Indonesia with a fairly high prevalence. The consequences of stunting can lead to poor child development and affect learning abilities, increased risk of infection and non-communicable diseases in adulthood, and reduced productivity. Changes in community behavior through health promotion programs and community empowerment about the importance of fulfilling nutritional status can help reduce stunting in children. Aim: The purpose of this study is to examine the literature, articles and research documents regarding the latest intervention activities to improve public attitudes and knowledge in stunting prevention. Method: The research method used is Literature Review. The data used comes from reputable journal articles through databases of international journal providers such as Google Scholar and SINTA published in the last 5-year period (2017-2022). Analysis of research results using the PICO-T method (Population, Intervention, Compare/intervention, Outcome, Time). Results: The results of the 10 research journals analyzed showed that the interventions provided varied greatly in terms of content, methods, media and duration. Interventions carried out in the form of audiovisuals, demonstrations, questionnaires and the provision of processed home products were able to increase knowledge and attitudes about stunting prevention. Conclusion: The conclusion of this study is that intervention in stunting prevention efforts is to provide education/health promotion, demonstrations of the creation of balanced complementary food and the empowerment of the community and posyandu cadres can significantly increase stunting prevention efforts